2021
DOI: 10.5194/bg-18-4717-2021
|View full text |Cite
|
Sign up to set email alerts
|

Blue carbon stocks and exchanges along the California coast

Abstract: Abstract. Salt marshes and seagrass meadows can sequester and store high quantities of organic carbon (OC) in their sediments relative to other marine and terrestrial habitats. Assessing carbon stocks, carbon sources, and the transfer of carbon between habitats within coastal seascapes are each integral in identifying the role of blue carbon habitats in coastal carbon cycling. Here, we quantified carbon stocks, sources, and exchanges in seagrass meadows, salt marshes, and unvegetated sediments in six bays alon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 84 publications
0
16
0
Order By: Relevance
“…This is likely due to a change in grain size moving upstream, from predominantly sandy to silty (Ward et al. 2021 ), and shows that in Elkhorn Slough, the ability of eelgrass to shift sediment properties is context dependent (Appendix S1 : Fig. S9).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is likely due to a change in grain size moving upstream, from predominantly sandy to silty (Ward et al. 2021 ), and shows that in Elkhorn Slough, the ability of eelgrass to shift sediment properties is context dependent (Appendix S1 : Fig. S9).…”
Section: Discussionmentioning
confidence: 99%
“…To convert percent TOM to percent organic carbon (OC), we used a power model (y=0.22normalχ1.1) derived using regional core data (Ward et al. 2021). Carbon storage was calculated by multiplying percent OC and the bulk density of each interval, reported as kg OC/m 3 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, autochthonous sources are expected to dominate sedimentary OM in salt marshes (Kelleway et al 2017a), but deposition of imported OM in form of Ulva spp. (Watson et al 2015) and seagrass wrack (Ward et al 2021) is known to occur in Eastern Pacific salt marshes. The incorporation of seagrass detritus into marsh surface sediments is not widely reported and previous studies suggest both negative (Macreadie et al 2013) and positive (Chapman and Roberts 2004) impacts of seagrass wrack on salt marsh productivity.…”
Section: Sources Of Om To Salt Marsh Sedimentsmentioning
confidence: 99%
“…Depending on soil characteristics, this can drive differences in SOM stocks apparent between east and west coast marshes. For instance, recent studies reported carbon densities four times greater in Northeastern than Californian salt marsh habitats [111,112]. This study found soil carbon inventories that were six times higher in NY than in CA (CA mean = 2500 g m -2 vs. NY mean = 16,000 g m -2 for the top 20 cm).…”
Section: Regional Differencesmentioning
confidence: 48%